RECONSTRUCTION OF PRINCIPLES OF LEGALITY IN CRIMINAL LAW BASED ON JUSTICE VALUE OF PANCASILA - muhammad yahya selma (UNISSULA, 2017)
Amendment of the Constitution 1945 after the fourth amendment, reinforce the concept of the state law and put it in Article 1 paragraph 3 of the Constitution of the Republic of Indonesia in 1945 which reads :